Pola Komunikasi Pemerintah Kalurahan Baturetno, Kapanewon Banguntapan, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Irvan Riyadi, Ade Chandra (Jurnal Masyarakat dan Desa, 2022)
TThe challenges faced by village governments in implementing development programs are increasingly complex, including the speed and quality of service to the community with digitalization. For this reason, good communication between lines in village government as an organization is not just a meaningless routine. This research focuses on Communication Patterns of the Baturetno Village Government, Banguntapan, Bantul. This research is using descriptive qualitative method. A total of 5 informants as village officials according to their field of work. Data collection through observation and interviews. The results of the research show that the pattern of communication is coordinated between structures with the principle of openness and takes place in an intimate manner. The communication of Baturetno Village Government reflects a pattern of two-way reciprocal coordinative communication between organizational structures, both vertically and horizontally